2020
DOI: 10.3389/fchem.2020.00737
|View full text |Cite|
|
Sign up to set email alerts
|

Opium Alkaloids in Harvested and Thermally Processed Poppy Seeds

Abstract: The opium alkaloids (morphine, codeine, thebaine, noscapine, and papaverine) have been detected on poppy seeds; they are widely used by the food industry for decoration and flavor but can introduce opium alkaloids into the food chain. Of the opium alkaloids found on poppy seeds, morphine, and codeine are the most pharmacologically active and have been detected in biological matrices collected in workplace and roadside drug testing resulting in positive opiate results. The European Food Safety Authority introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 40 publications
8
27
1
1
Order By: Relevance
“…Due to the surface contamination and the large number of other factors influencing the concentration of these alkaloids in poppy seeds, variable amounts have been found in the same batch of seeds. For these reasons, the range of concentration is provided to show the extent of the variation and is in accordance with other researchers who identified a variation in opium alkaloids within a batch and between batches of poppy seeds analysed [1,2,44]. Concentrations of morphine ranged from 1.5 to 249.0 mg/kg, codeine from <0.…”
Section: Application Of the Methods Sle-mspe-uhplc-qqq-ms/ms To Real Samples Of Poppy Seedssupporting
confidence: 85%
See 1 more Smart Citation
“…Due to the surface contamination and the large number of other factors influencing the concentration of these alkaloids in poppy seeds, variable amounts have been found in the same batch of seeds. For these reasons, the range of concentration is provided to show the extent of the variation and is in accordance with other researchers who identified a variation in opium alkaloids within a batch and between batches of poppy seeds analysed [1,2,44]. Concentrations of morphine ranged from 1.5 to 249.0 mg/kg, codeine from <0.…”
Section: Application Of the Methods Sle-mspe-uhplc-qqq-ms/ms To Real Samples Of Poppy Seedssupporting
confidence: 85%
“…In the case of morphine, wide ranges of concentrations were obtained by López et al; 0.2–241 mg/kg, Sproll et al; between <1 and 270 mg/kg, Bjerver et al who found 2.6–106.7 mg/kg; and Hayes et al between 17 and 294 mg/kg [ 1 , 6 , 45 , 46 ]. Lower results were found by Carlin et al between 3 and 64 mg/kg [ 44 ] and higher levels were found by Powers et al from <1 to 2788 mg/kg [ 3 ]. Regarding codeine, the results obtained were very similar to the results obtained by Sproll et al, who found <0.3–56 mg/kg [ 6 ] but were lower than the results found by López et al who found from <0.1 to 348 mg/kg and Powers et al from <1 to 247.6 mg/kg [ 1 , 3 ].…”
Section: Resultsmentioning
confidence: 93%
“…Due to its toxic effects above certain thresholds as well as the potential for confounding drug tests for opiates (Lachenmeier et al, 2010), this question is of significant importance regarding acceptable levels for products intended for baking purposes. While previous literature has generally assumed a considerable decrease of morphine and other alkaloids during baking (Brenneisen and Borner, 1985;Kniel, 2006;Sproll et al, 2006Sproll et al, , 2007Carlin et al, 2020), new data from the U.S. Food and Drug Administration (FDA) (Shetge et al, 2020; also see discussion in Kleinmeier et al, 2021) has shed doubt on this opinion as opiate levels were quite stable when incorporated into a model baked product. Kleinmeier et al (2021) tried to explain this discrepancy by the possible confounding of previous baking experiments by processing steps including soaking of the poppy seeds, which has been reported to reduce opium alkaloids on the surface of poppy seeds.…”
Section: A Commentary Onmentioning
confidence: 99%
“…All the parts of the plant contain alkaloids, with the highest amount being found in the capsules [ 1 ]. Even its seeds - used as condiments for cooking- contain some quantity, but they don’t exceed the recommended reference dose of morphine in food products (10 μg morphine/kg of body weight) [ 31 ]. Opium contains more than 42 individual alkaloids and a much higher quantity of Morphine than the pods [ 1 , 15 , 32 ].…”
Section: Comments About Opium’s Toxicitymentioning
confidence: 99%